2016
DOI: 10.1158/1541-7786.mcr-15-0380
|View full text |Cite
|
Sign up to set email alerts
|

miR-137 Regulates the Tumorigenicity of Colon Cancer Stem Cells through the Inhibition of DCLK1

Abstract: miRNAs have important roles in regulating cancer stem cell (CSC) properties and are considered to be potential therapeutic targets. However, few studies have focused on miRNAs which are specifically related to colon CSCs. Here, a PCR-based miRNA profiling analysis of normal colon stem cells (NCSC) and colonÀ ) identified miRNAs which regulate colon CSC properties. Interestingly, miRNA-137 (miR-137) expression was downregulated in the colon CSCs compared with NCSCs, while doublecortin-like kinase 1 (DCLK1) mRNA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 34 publications
(33 reference statements)
1
57
0
Order By: Relevance
“…Recent studies provide strong evidence that DCLK1 is involved in tumor progression and can be regarded as a CSC marker [11][12][13]17]. In this study, we found that DCLK1 was overexpressed in pancreatic cancer, correlating with metastasis and prognosis.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…Recent studies provide strong evidence that DCLK1 is involved in tumor progression and can be regarded as a CSC marker [11][12][13]17]. In this study, we found that DCLK1 was overexpressed in pancreatic cancer, correlating with metastasis and prognosis.…”
Section: Discussionsupporting
confidence: 51%
“…Accumulating evidence suggests that CSCs are responsible for cancer metastasis, recurrence and radio/chemo-resistance [36][37][38], and previous reports demonstrate that DCLK1 can mark CSCs in gastrointestinal and other cancers [12][13][14]. A recent study revealed that DCLK1 is essential for the invasive and metastatic properties of CSCs in human pancreatic cancer and that it might be a promising therapeutic target [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One study utilized PCR-based miRNA profiling analysis of normal colon stem cell (NCSCs) and colon CSCs (EpCAM+/CD44+/CD66a-) to identify miR-137 (miRNA-137), which serves to regulate colon CSC properties [16] . MiR-137 was downregulated in the colon CSCs compared to NCSCs.…”
Section: Non-coding Rna and Cscsmentioning
confidence: 99%